Green Innovation Strategy and Supply Chain Resilience: The Roles of Green Logistics Management Practices and Supply Chain Complexity - Putri, Dewi Sabrina Eka; Widowati, Dorina; Santosa, Wahyuningsih; Darasih, Ratna (Golden Ratio of Data in Summary, 2026)
This study aims to examine the effect of Green Innovation Strategy on Supply Chain Resilience by considering the mediating role of Green Logistics Management Practices and the moderating role of Structural and Dynamic Supply Chain Complexity in manufacturing firms. The research was conducted in a tire yarn manufacturing company located in Citeureup, Bogor Regency, Indonesia, involving 203 employees across various operational levels. Data were collected using a structured questionnaire distributed through purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that: (1) Green Innovation Strategy positively influence Green Logistics Management Practices, (2) Green Innovation Strategy positively influence Supply Chain Resilience, (3) Green Logistics Management Practices positively influence Supply Chain Resilience, (4) Green Logistics Management Practices mediate the relationship between Green Innovation Strategy and Supply Chain Resilience, (5) Structural Supply Chain Complexity moderates the relationship between Green Innovation Strategy and Green Logistics Management Practices, and (6) Dynamic Supply Chain Complexity moderates the relationship between Green Logistics Management Practices and Supply Chain Resilience. This study contributes to the green supply chain management literature by providing an integrated framework that links green innovation, logistics practices, and supply chain complexity in explaining supply chain resilience. Practically, the findings offer insights for manufacturing managers in designing integrated green strategies to enhance supply chain resilience in complex and dynamic environments.